Urinary phthalate concentrations and mortality risk: a population-based study - Beyer, Anika; Schorgg, Paula; Karavasiloglou, Nena; Sarwar, Sneha; Rohrmann, Sabine; Bärnighausen, Till; Cassidy, Aedin; Connolly, Lisa; Kühn, Tilman (SSRN, 2022)
Phthalates are widely used as plasticizers. Laboratory-based mechanistic and epidemiological studies suggest that phthalates are detrimental to human health. Here, we present prospective analyses on phthalate exposure and all-cause, as well as cause-specific, mortality from the National Health and Nutrition Examination Survey (NHANES), a population-based cohort. Between 1999 and 2010, urinary concentrations of 15 phthalate metabolites were measured by high-performance liquid chromatography-electrospray ionization tandem mass spectrometry in spot urine samples of 6,314 adults aged 40 to 85 years, of which 1,441 died over a median follow-up duration of 9.8 years. Multivariable Cox regression analyses adjusted for a wide range of lifestyle factors and comorbidities showed that higher concentrations of mono-benzyl phthalate (MBzP) were associated with increased mortality. The hazard ratios for participants in the highest quartile of MBzP concentrations were at 1.25 [95% confidence interval: 1.07, 1.46; p linear trend = 0.01] for all-cause mortality and 1.29 [0.92, 1.81; p linear trend = 0.01] for cancer mortality. In addition, higher concentrations of Mono-(2-ethyl-5-oxohexyl) phthalate (MEOHP, 1.84 [1.17, 2.90]; p linear trend = 0.02) and Mono-isobutyl phthalate (MiBP, 1.73 [1.01, 2.96; p linear trend = 0.02]) were positively associated with cardiovascular mortality. These findings reinforce the need for a regulation of phthalate use